2015
DOI: 10.1007/s12022-015-9383-6
|View full text |Cite
|
Sign up to set email alerts
|

Immune Cell Infiltrates in Pituitary Adenomas: More Macrophages in Larger Adenomas and More T Cells in Growth Hormone Adenomas

Abstract: Tumor immune microenvironment has been gradually recognized as a key contributor to tumor development, progression, and control. Immune cell infiltrates in brain tumors have been increasingly studied, but few have published on immune cell infiltrates in pituitary adenomas. We quantitatively assessed the infiltration of macrophages and lymphocytes in 35 pituitary adenomas, including 9 densely granulated growth hormone (DG-GH), 9 sparsely granulated growth hormone (SG-GH), 9 null cell (NC), and 8 adrenocorticotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
71
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(83 citation statements)
references
References 35 publications
6
71
1
Order By: Relevance
“…Functional subtypes (e.g. GH adenomas) appear to demonstrate greater degrees of lymphocyte infiltration than non-functional tumors [32]. In our study, functional pituitary tumors exhibited more frequent lymphocytic infiltration than non-functional tumors, consistent with previous observations [31].…”
Section: Discussionsupporting
confidence: 91%
“…Functional subtypes (e.g. GH adenomas) appear to demonstrate greater degrees of lymphocyte infiltration than non-functional tumors [32]. In our study, functional pituitary tumors exhibited more frequent lymphocytic infiltration than non-functional tumors, consistent with previous observations [31].…”
Section: Discussionsupporting
confidence: 91%
“…A study on a cohort of 291 PitNET patients showed that TILs were more abundant in PitNETs compared with the normal pituitary gland and that TILs were associated with a poorer clinical outcome, although a pan-lymphocyte marker was employed, limiting further conclusions [33]. Another study on 35 PitNETs, including 18 somatotroph tumours, showed a positive correlation between the number of infiltrating CD68+ macrophages and tumour size and invasiveness [34]. In the same study, somatotroph tumours were shown to have a higher number of infiltrating CD4+ and CD8+ TILs compared with non-somatotroph tumours.…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] Both the CD4 + and CD8 + lymphocytes were frequently observed in GH-secreting pituitary adenomas. [ 17 ] The inhibition of PD-1 signaling pathways could help CD8 + lymphocytes recognize and kill tumor cells. [ 15 , 18 ] Moreover, blockade of the PD-1 signaling pathways was also substantial for macrophages to inhibit tumor development.…”
Section: Discussionmentioning
confidence: 99%